Retracted: Characterization of the Interaction between RIN13 (RPM1-Interacting13) and Sumo Proteins in Arabidopsis thaliana. This article has been retracted at the request of the author. The reason is due to poor quality of the publication, which may reflect poorly on the scientific quality of the authors. - Santosa, Venny; Nagabuchi, Mio; Okada, Sachiko; Tanaka, Katsunori (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
.